PERKEMBANGAN PSIKO-FISIK SISWA - Prastyawan Prastyawan (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Abstract: The development of psycho-physical thought to have a direct relationship with student learning activities; these developments are the physical motor development of students. There are four kinds of factors that encourage the continuation of the development of motor skills of children, growth and development of the nervous system, muscle growth, development and growth of endocrine gland function, and changes in physical structure.Further development is very important for students are cognitive. A psychiatric domain that is domiciled in this brain, in the perspective of cognitive psychology, is the source while controlling other psychiatric domains. Without the cognitive is hard to imagine a student is able to think. Further development is as important as the moral and social development of students. The process of social and moral development is always associated with the learning process. This means that the learning process is to determine the ability of students in attitude and social behavior that is consistent with the norms of morality, religion, moral tradition, the moral law and moral norms that exist in society.